Fashion and textile design with Photoshop and Illustrator : professional creative practice - Hume, Robert (New York : Bloomsbury Publishing Plc, 2020)
"Designer and educator Robert Hume guides you from novice to expert through twenty carefully crafted projects. You'll start by mastering layers and custom brushes, learning about stripes and weaves, scanning and manipulation before moving on to repeats, colorways, and simple geometry. Next, transformations, filters and effects become tools for your personal creativity and you'll explore varied approaches to drawing garments. Finally, you'll learn about key layout and presentation techniques in both programs. There's also advice on sharing, communication and output, and help with diagnosing and correcting common problems"--